TAMI-14. NANOPARTICLE DELIVERY OF PD-L1 CRISPR/CAS9 PLASMID DNA FOR ANTI-GLIOBLASTOMA IMMUNOTHERAPY. (9th November 2020) - Fierro, Javier; Tran, An; Factoriza, Chris; Chin, Brandon; Dou, Huanyu
Abstract: Glioblastoma multiforme (GBM) is a devastating cancer that develops from astrocytes in the brain. GBM is fast acting and kills 90% of patients within 5 years. Several immunotherapies have been developed to treat GBM, however, major challenges still persist. For example, checkpoint proteins such as programmed cell death protein 1 (PD-1) and its ligand, programmed death ligand 1 (PD-L1), are upregulated in GBM cells to evade the immune system. Targeting PD-L1 for genetic knockdown is thus a promising avenue for the treatment of GBM. However, PD-L1 protein inhibitors have been shown to cause immune overreaction and toxicity, therefore requiring new technologies. CRISPR/Cas9 gene editing has been widely used for the study and treatment of many diseases, but has not been extensively studied for the treatment of GBM. The main challenge is developing a gene delivery platform for the delivery of CRISPR/Cas9 plasmid DNA (pDNA). Many viral vectors have been used for the delivery of pDNA, but unfortunately are associated with high toxicity. Nanotechnology is emerging as a new platform for the delivery of pDNA as it shows high transfection efficiency with low cytotoxicity. We developed a cationic core-shell nanoparticle (NP) capable of carrying CRISPR/Cas9 pDNA. This plasmid contains multiple guide RNA (gRNA) expression cassettes for the knockdown of PD-L1. PDL1gRNA-CRISPR/Cas9pDNA-NPs were taken up by U87 cells within 30 minutes, and entered into the nucleus at 2 hours. The effective delivery of PDL1gRNA-CRISPR/Cas9pDNA-NPs led to the expression of PD-L1 gRNA and Cas9 enzyme, and the knockdown of PD-L1. Regulation of immune balance was determined after PD-L1 knockdown in vitro and in vivo . Our study shows the potential of NP-based PDL1gRNA-CRISPR/Cas9 delivery as an anti-GBM immunotherapy for clinical applications.